Home-based virtual reality exercise program during the maintenance stage of cardiac rehabilitation: A randomized controlled trial - Vieira, Ágata (2023)
Home-based virtual reality technology may become an alternative to cardiac rehabilitation. To evaluate the effects of a specific, home-based exercise program, performed either through a virtual reality (Kinect) or a conventional format (booklet) in the maintenance stage of cardiac rehabilitation for six months on functional muscle strength of the lower limbs, physical activity and exercise tolerance. This is a randomized clinical trial (ClinicalTrials.gov — NCT02753829) with individuals with coronary artery disease from a hospital in Porto, Portugal, randomly allocated to an experimental group “1” (EG1; n = 11), submitted to a virtual reality exercise program (Kinect); an experimental group “2” (EG2; n = 11), submitted to an exercise program described in a booklet (conventional format); or a control group (CG) (n=11), submitted to routine care. Parameters of functional muscle strength of the lower limbs (sit-to-stand test), physical activity (accelerometer) and exercise tolerance (stress test) were assessed and compared between the groups. Descriptive and inferential statistics were applied, with 95% with a significance level of 0.05. Significant improvements in functional muscle strength of the lower limbs were observed in EG1 compared to EG2, at three months (19.5 ± 7.7 versus 11.9 ± 4.7, p = 0.042), and at six months (23.0 ± 7.7 versus 14.6 ± 4.6, p = 0.027) of intervention. The program did not demonstrate superior results, in relation to the control group and among the different formats, in physical activity and effort tolerance. In relation to the functional muscle strength of the lower limbs, the virtual reality format showed significantly better results when compared to the conventional format only.